"The picture of Carthage in the work of Dracontius" - (:unkn) unknown (My University, 2021)
Dracontius, the most important poet of the Vandal Kingdom in Africa, does not describe Carthage – he composes no ekphrasis – but he certainly evokes the city: Punic Carthage through historic exempla (Dido, the Punic wars, the sacrifice of children); the urban landscape of Carthage under the Vandals through a few mentions of public monuments, with particular stress on the ramparts (moenia). Dracontius offers a picture of it which is very different from that of younger poets in the Latin Anthology (Felix, Florentinus, Luxorius). They praise the Vandal kings whereas Dracontius uses his words to create a picture of Roman Carthage which ignores the Vandal period; but this picture is not an idealised one, as Dracontius also reveals a climate of politico-religious tensions.
Keywords: African Research